Analysis the Implementation of the Independent Learning Curriculum in Grade IV SDN Inpres 2 Talise - Rafika Langimpu; Pahriadi Pahriadi; Rizal; Surahman (CV. Dharma Samakta Edukhatulistiwa, 2025)
The problem in this study is how is the implementation of the Merdeka Belajar Curriculum in grade IV SDN Inpres 2 Talise? This study aims to describe how the implementation of the Independent Learning Curriculum in grade IV SDN Inpres 2 Talise. The type of research used is qualitative research with data collection methods, namely observation, interviews, and documentation. After the data is collected, data analysis techniques are carried out, namely data collection, reduction, and inference. The results of this study show that the implementation of the Independent Learning Curriculum in grade IV has been carried out and is included in the good category with a percentage result of 84%. Teachers have implemented the Strengthening Pancasila Student Profile (SPSPP) Project, carried out differentiated learning, created an interesting learning environment, and understood students' literacy and numeracy skills. As for the difficulties in the implementation of the Independent Learning Curriculum in grade IV is the creation of teaching modules and the creation of SPSPP reports. And the obstacle is the lack of participation of parents in the learning process.